A case study for measuring and evaluating map skills of primary school children - Senol, Halil Ibrahim; Gokgoz, Turkay (Geomatik Journal, 2022)
In this study, map drawing and reading skills of primary school students were tried to be determined. In accordance with this purpose, children were firstly given home-to-school arrival routes task (home-school maps) and the results were evaluated according to various criteria. Secondly, they were asked to draw exactly what they saw on a printed World map and the results were again evaluated according to various criteria. Finally, an object was hidden in a certain point of the class and they were asked to find the object by using an existing map (approximate scale class plan). As a result, it was found that the quality was not increasing in proportion to age in the maps drawn by students (home-school and World maps) and most of them were of medium quality. However, it was observed that the students were quite good in terms of using a map.
Keywords: Cartography; Map Activities; Topological Relations; Map Skills; Geology; Remote Sensing